2005
DOI: 10.1111/j.1365-2664.2005.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Why high seed densities within buried mesh bags may overestimate depletion rates of soil seed banks

Abstract: Summary 1.Estimates of seed bank depletion rates are essential for modelling and management of plant populations. The seed bag burial method is often used to measure seed mortality in the soil. However, the density of seeds within seed bags is higher than densities in natural seed banks, which may elevate levels of pathogens and influence seed mortality. The aim of this study was to quantify the effects of fungi and seed density within buried mesh bags on the mortality of seeds. Striga hermonthica was chosen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 23 publications
1
96
0
Order By: Relevance
“…Van Mourik et al (2005) observed that high seed densities placed in bulk in nylon bags lost viability rapidly due to the attack of soil fungi. In accordance with that author, at densities around 1,000 seeds per nylon bag, the mortality rate is extremely high.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Van Mourik et al (2005) observed that high seed densities placed in bulk in nylon bags lost viability rapidly due to the attack of soil fungi. In accordance with that author, at densities around 1,000 seeds per nylon bag, the mortality rate is extremely high.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with that author, at densities around 1,000 seeds per nylon bag, the mortality rate is extremely high. In the present study, using the same permeable nylon bags recommended by Van Mourik et al (2005) with seeds placed in five different vertical positions, instead of bulk, the attack of fungi was supposed to be reduced. However, the idea of removing the forage mass, in an attempt to keep the pasture height similar to the adjoining grazing area, was not completely achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In drier, unimodal rainfall areas 1 of Benin, S. hermonthica seed viability declined from 90 to 15 % over 6 months (Gbèhounou et al 1996a), with almost total loss of viability over two wet seasons (Gbèhounou 1998). Reasons for the discrepancy were resolved by showing that burial of S. hermonthica seeds in small mesh packets, as in the Benin and Western Kenyan reports, leads to rapid loss of viability associated with microbial decay (van Mourik et al 2005).…”
Section: Seed Survival In Moist Storagementioning
confidence: 99%